PENGARUH PEMBUANGAN PUCUK DAN TUNAS KETIAK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CABAI - Muhammad Hatta (Jurnal Floratek, 2012)
This study was aimed to examine effects of terminal bud and auxiliary shoot removals on growth and yield of chili pepper. The experiment was arranged in a randomized complete block design (RGD) with 3 replications. Factors studied were trimming of terminal bud and trimming of auxiliary shoots.   Results showed that removal of terminal bud had no effect on plant growth, represented by stem diameter (P = 0.6517) and yields, represented by the number of fruits (P = 0.9806) and length of fruit (P = 1128). Similarly, removal of auxiliary shoots also had no effect on stem diameter (P = 0.7302), number of fruits (P = 0.4210), and length of fruit (P = 0.9878).